2021
DOI: 10.1063/5.0071801
|View full text |Cite
|
Sign up to set email alerts
|

Experimentally investigating the performance degradations of the CMOS PA at different temperatures

Abstract: To investigate the temperature dependency of the specifications for Power Amplifiers (PAs), the performance degradations of an IC PA under different temperature conditions are investigated experimentally. The experimental results show that the performance degradations of the PA are sensitive to temperature changes. The main reasons for these degradations are discussed and analyzed in this paper. The research performed in the study provides another angle to handle the practical working environments rather than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Literature studies have shown [ 37 ] that the on-state resistance between source and drain increases with temperature, which leads to a drop in the P out . The expression for on-resistance is [ 37 ] where the constant k is a process parameter, R 0 is a constant independent of voltage and temperature, α ≈ 1.5, β ≈ 0.2, V gs is the gate voltage, and V th is the threshold voltage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature studies have shown [ 37 ] that the on-state resistance between source and drain increases with temperature, which leads to a drop in the P out . The expression for on-resistance is [ 37 ] where the constant k is a process parameter, R 0 is a constant independent of voltage and temperature, α ≈ 1.5, β ≈ 0.2, V gs is the gate voltage, and V th is the threshold voltage.…”
Section: Resultsmentioning
confidence: 99%
“…The specific reasons are discussed below. Literature studies have shown [37] that the on-state resistance between source and drain increases with temperature, which leads to a drop in the P out . The expression for on-resistance is [37] R…”
Section: Output Power and Pae At Different Temperaturesmentioning
confidence: 99%
“…Recently, the influence of temperature on PA has been discussed. It has been also reported that the rising temperature can lead to the performance degradation of PA 10–15 . However, the methods presented in similar literatures all need much measurement time to obtain the performance varitions 6,12,13,15 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the methods presented in similar literatures all need much measurement time to obtain the performance varitions 6,12,13,15 . This drawback causes the characteristics to be studied only at certain temperatures 6,10–16 . Moreover, considering the limitation of experimental devices, it is almost impossible to measure all the data.…”
Section: Introductionmentioning
confidence: 99%
“…According to previous papers, investigation on temperature behavior is still a hot issue [ 9 , 10 ]. However, the common temperature ranges, depending on the extreme temperature, are −40–120 °C, −25–125 °C, 10–90 °C, 20–120 °C or 25–125 °C and so on [ 8 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Meanwhile, the equal interval temperatures are adopted [ 8 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%